2019
DOI: 10.3390/coatings9060397
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties of Pine Scrimber Panels with Varying Density

Abstract: Coating quality for scrimber products against exterior conditions is largely dependent on the surface properties. The wettability, morphology, and chemical composition of pine scrimber surfaces were investigated to better understand the surface properties. The scrimber was found to be a hydrophilic material because the water contact angles were less than 90°. The panels with a density of 1.20 g/cm3 had the largest angle change rate (k = 0.212). As the panel density increased, the instantaneous contact angle of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Roughness depends on the material properties (e.g., density and porosity) and surface machining (e.g., sawing, planning, and sanding) [29,30]. Previous studies have found that high-density woody composites had low surface wettability and there is a strong correlation between the density and wettability [31,32]. Bamboo scrimber is a high-density composite composed of bamboo and phenolic resin, in which there are complex physical and chemical interactions between the two components.…”
Section: Introductionmentioning
confidence: 99%
“…Roughness depends on the material properties (e.g., density and porosity) and surface machining (e.g., sawing, planning, and sanding) [29,30]. Previous studies have found that high-density woody composites had low surface wettability and there is a strong correlation between the density and wettability [31,32]. Bamboo scrimber is a high-density composite composed of bamboo and phenolic resin, in which there are complex physical and chemical interactions between the two components.…”
Section: Introductionmentioning
confidence: 99%